Risk Factors for Stunting and Severe Stunting among Children (12-59 Months Old) in the Coastal Area of Surabaya, East Java, Indonesia - Has, Eka Mishbahatul Mar’ah; Prakhasita, Ridha Cahya; Krisnana, Ilya; Wahyuni, Sylvia Dwi; Arief, Yuni Sufyanti; Nursalam, Nursalam (International Journal of Psychosocial Rehabilitation, 2020)
The prevalence of children with stunting in Indonesia has remained high over the past decade, especially in coastal areas. This study aimed to analyze factors which correlate with stunting and severe stunting among children (12-59 months old) who lived in the coastal area of Surabaya, East Java, Indonesia. This was a descriptive-analytic study with a cross-sectional approach. The study enrolled 85 mother-child pairs with children aged 12-59 months old with stunting using a multistage random sampling technique. The independent variables were child’s age, sex, birth order, mother’s age, mother’s level of education, complementary feeding practice, number of children under five years old at home, family size, and family’s income; the dependent variable was the level of stunting. All of the socio-demographic data were gathered using a questionnaire. Complementary feeding practices were assessed with the Child Feeding Questionnaire. Children’s height was measured with an infantometer. Nominal logistic regression test showed that factors which correlate with stunting and severe stunting among children aged 12-59 months old include birth order (first and second child), and sub-optimal complementary feeding practice. First and second children were less likely to experience severe stunting (OR 0.035; 95% CI 0.003-0.36 and OR 0.003; 95% CI 0.00-0.02). Children with sub-optimal complementary feeding practice had higher odds for severe stunting (OR 2.477; 95% CI 2.42- 58.48). Reducing birth rates which limit birth order and providing appropriate complementary feeding practice is important in reducing stunting in the coastal areas of Surabaya. Hence, health promotion programs to address these findings should be designed comprehensively.